A comparison of ringed and bearded seal diet, condition and productivity between historical (1975–1984) and recent (2003–2012) periods in the Alaskan Bering and Chukchi seas. (August 2015) - Crawford, Justin A.; Quakenbush, Lori T.; Citta, John J.
Highlights: Ringed seals ⩾1 year of age are eating more (%FO) Arctic cod ( Boreogadus saida ). Ringed seals are growing faster, have thicker blubber, and females mature earlier. Ringed seal growth and the proportion of pups harvested decreased with heavier ice. Bearded seals ⩾1 year of age are eating fewer (%FO) invertebrates (10 of 24 taxa). Bearded seals have thicker blubber and females mature earlier now. Abstract: Reductions in summer sea ice in the Chukchi and Beaufort seas are expected to affect what has been an ice-adapted marine food web in the Pacific Arctic. To determine whether recent decreases in sea ice have affected ice-associated marine predators (i.e., ringed, Pusa hispida, and bearded seals, Erignathus barbatus ) in the Bering and Chukchi seas we compared diet, body condition, growth, productivity, and the proportion of pups harvested (an index of weaning success) for seals of each species harvested by 11 Alaskan villages during two periods; a historical (1975–1984) and a recent period (2003–2012). We also examined how changes in indices of seal health may be correlated with the reduction of sea ice characteristic of the recent period. For ringed seals ⩾1 year of age, the % frequency of occurrence (%FO) of Arctic cod ( Boreogadus saida ), walleye pollock ( Gadus chalcogramma ), rainbow smelt ( Osmerus mordax ), and Pacific herring ( Clupea pallasi ) increased from the historic to the recent period, while the %FO of invertebrates decreased for both pups and seals ⩾1 year of age. For bearded seals ⩾1 year of age, the %FO of Arctic cod, pricklebacks, and flatfish increased during the recent period, while the %FO of saffron cod ( Eleginus gracilis ) decreased for pups. Although invertebrates did not change overall for either age class, decreases occurred in 10 of 24 specific prey categories, for bearded seals ⩾1 year of age; only echiurids increased. The %FO of gastropods and bivalves increased for pups while isopods and one species of shrimp and crab decreased in occurrence. During the recent period ringed seals grew faster, had thicker blubber, had no change in pregnancy rate, matured 2 years earlier, and a larger proportion of pups was harvested than during the historical period. Correlations with spring ice concentration showed that the growth and blubber thickness of seals ⩾1 year of age, blubber thickness of pups, and the proportion of pups in the harvest all declined for ringed seals when ice concentrations were higher in the historic period. However, only the correlations between high ice concentrations and growth of ringed seals ⩾1 year of age and the proportion of ringed seal pups in the harvest were statistically significant. Although growth of bearded seals ⩾1 year of age was slower during the recent period, it was similar to the average over the entire time series, and blubber thickness increased. Pup growth and blubber thickness did not change between periods. There was no change in pregnancy rate, but females matured 1.6 years earlier, and a larger proportion of pups were harvested. Correlations with spring ice concentration showed that the growth of seals ⩾1 year of age, the growth of pups, blubber thickness of pups, and proportion of pups in the harvest also declined for bearded seals when sea ice concentrations were higher. However, no relationships between bearded seals and sea ice were statistically significant. Overall, our results suggest that ringed seals in the Alaskan Bering and Chukchi seas have adjusted to changes in diet, are growing faster and possibly weaning more pups in the recent compared to the historic period. These patterns are less evident for bearded seals. Although the ringed and bearded seals we examined have not exhibited the declines in body condition, growth, or reproduction observed in other populations, continued monitoring and comparison among seal populations is vital to understanding the effects of changing environmental conditions in the Pacific Arctic region.